Eficácia e segurança do extrato etanólico de tocoyena sellowiana em ensaio pré-clínico de periodontite: análise do envolvimento de prostaglandina e2 (pge2) e interleucina 1 beta (il-1β) - Ribeiro, Debora da Silva Freitas (2013)
Periodontitis is a chronic inflammatory process that affects the supporting tissues of the teeth characterized by extensive alveolar bone resorption. The Tocoyena sellowiana (Ts) is a small tree belonging to Rubiaceae family, popularly known as typical angry genipapo, Cerrado, whose stem bark is used in folk medicine as anti - inflammatory agent. This study aimed to evaluate the efficacy and safety of the ethanol extract of the stem bark of Tocoyena sellowiana in a pre-clinical trial of periodontitis. Periodontitis (PE) was induced by placing a nylon thread (3.0) on the upper molars of Wistar rats (200-220 g). Animals were weighed and treated (per os) daily for 11 days, with Ts (0.1, 1 or 10 mg/kg). The untreated group underwent induction of periodontitis and treated (per os) daily for 11 days with vehicle (saline). Alveolar bone loss, serum bone alkaline phosphatase (FAO), PGE2, IL-1β, myeloperoxidase (MPO), immunohistochemical analysis for COX-2, and safety assessment of Ts: the following parameters were analyzed. The Ts (0.1, 1 or 10 mg / kg ) reduced (p< 0.05) bone loss (4.96 ± 0.39, 3.89 ± 0.13 and 1.74 ± 0.15 respectively) , compared to the control group (7.09 ± 0.43), animals treated with Ts (10 mg/kg) had a significant increase (p< 0.05) of the variation of the FAO (6.99 ± 65.3) compared to the untreated group and (33.6 ± 6.91) . Ts (10 mg/kg) decreased (p<0.05) levels in gingival samples of PGE2 (212.3 ± 2.26), compared with the untreated group (355.7 ± 4.33). Ts (10 mg/kg) decreased (p <0.05) levels of IL-1β in gingival samples (237.4 ± 0.86), compared with the untreated group (868.1 ± 1.99). Ts (10 mg/kg) decreased marking COX-2 when compared with the untreated group. Ts (10 mg/kg) decreased (p<0.05) levels of MPO in the gingival 6 hour samples (0.77 ± 7.38) compared with the untreated group (1.54 ± 21.1). No difference (p>0.05) between the serum levels of ALT/AST, creatinine and total alkaline phosphatase between treated groups and untreated Ts was observed. The animals treated with ST (10 mg/kg) had no change in hepatic, renal tissue, cardiac tissue and gastric mucosa as compared with animals in the untreated group. Our results suggest that Tocoyena sellowiana has protective effect on periodontitis by inhibiting PGE2, IL-1β, and MPO increased FAO, and represents a safe therapeutic option in the pre-clinical trial of periodontitis in rats.